Designing of the expert system "labor market monitoring" for formation of the state order for training of specialists (Pedagogy of Higher and Secondary Education, 2012)
Nyelyepova A. V., Tverezovska N. T. Designing of the expert system "labor market monitoring" for formation of the state order for training of specialists.Theoretical and methodological analysis of the components of the labor market are carried out, the relationship of vocational education and human capital formation is analyzed; policy implementation system of quality management training, determined by the requirements of the modern specialist, is defined; highlights the components of the expert system, «Monitoring the labor market», the issues the public order training are explored.
Keywords: expert system; input-output block; the block of data; analytical power; knowledge base; human capital; labor; infrastructure; labor market; human resources; monitoring of the labor market; the state order for training